Pengembangan Permainan Jenga Edukatif Berbasis Keterampilan dengan Tema 'Pahlawanku' untuk Siswa Sekolah Dasar - Pahri, Arnia; Rosdiana; A. Riawarda (Universitas KH. Abdul Chalim Pacet Mojokerto, 2023)
This research is based on developing thinking skills and developing jenga educational games based on the theme of my hero. The purpose is to analyze the needs, validity, and practicality of the development of thinking skills-based jenga educational games based on the theme of my hero. The type of assessment is research and development using the A.D.D.I.E. model (Analyze et al., and Evaluation), but only up to the 4th stage, namely implementation. Data collection is done using direct observation and interviews with fourth-grade teachers. While interview guidelines, student questionnaires, validation tests, and practicality tests are presented as instruments. The data analysis technique used is a mix method, which is a combination of qualitative and quantitative data. This research produced thinking skills-based jenga educational game media on the theme of my hero. This jenga educational game media was made and validated by three expert validators, namely design experts 90% (very valid), language experts 87.5% (very valid), and material experts 85% (very valid), then practicality was carried out by students to obtain a very practical category. The resulting product thus meets the criteria of validity and practicality, so that the jenga educational game media produced is said to be feasible and can be used.